Effects of cognitive ability, accessibility and utilisation of library information resources on administrative effectiveness of senior officers in local government areas in Ibadan metropolis (2019)
The main objective of the study is to investigate the effects of cognitive ability, accessibility and utilisation of library information resources on administrative effectiveness of senior officers in local governments in Ibadan metropolis. Total enumeration was used for the study because of the small size of the population of the senior officers in eleven local government areas in Ibadan metropolis. A total sample size of 234 was used. The questionnaire was used for data collection. Data was analysed using frequency distribution and regression analysis run on Statistical Package for Social Sciences(SPSS).The findings revealed that respondents generally have access to information resources.Larger proportion of the senior officers 161(73.2%) affirmed that local government authority organised training programme for effective administration. The most potent factors was types of information utilized (a = .484, p<0.05) followed by accessibility to information (a = 0.302, p<05), cognitive ability of Senior Officer ((a = 0.19, p < 0.05) and sources of information utilization (a= 0.086, p < 0.05). Correlation between administrative effectiveness of senior officers is also significant (r = 0.52, p < 0.05) while limited number of computers 115(52.3%), poor power supply 125(56.8%), unavailability of resource 136(61.8%) and lack of funds 102(46.4%>) were the major problems hindering administrative effectiveness.The study concluded that library and information professionals should know more about how senior officers in local government make use of information resources for effective administration and to guide the provision of information services in local governments.